Teachers’ Perception on Students’ Learning Style and Their Teaching - Agustrianita, Agustrianita; Suherdi, Didi; Purnawarman, Pupung (Curriculum and Educational Technology Department, 2019)
Lack of teachers? understanding in students? learning styles and their teaching could cause unfacilitated teaching methods for example through the use of traditional lecturing methods. This issue brings the importance of this research objective to investigate teachers? perceptions about learning style, their teaching, and the applied methods in the classroom. This study uses a quantitative research approach that is the analysis of learning style types for different students at different grade levels. To find out the perceptions of English teachers in this study, information was collected through 20 closed questions with data analysis to find out how the learning style influenced the teaching learning process of 28 English teachers. The findings of this study suggest that teachers? understand about students? different learning styles, so they adopt their students? learning styles to their teaching. The last, teachers agree to use group discussion rather than lecturing methods by integrating ICT. In conclusion, teachers? perception on students? learning styles can increase their awareness to design teaching methods that differentiate students? learning styles. Abstrak Kelangkaan pemahaman guru mengenai gaya belajar siswa dan bagaimana cara mengajarnya yang tepat dapat disebabkan oleh metode mengajar yang tidak bersifat fasilitatif, misalnya masih berupa perkuliahan tradisional. Oleh karena itu, penting untuk meneliti persepsi guru mengenai gaya belajar, cara mengajarnya, dan implementasinya di kelas. Penelitian ini menggunakan pendekatan kuantitatif yang fokus pada beragam gaya belajar siswa pada kelas-kelas yang berbeda. Infomasi diperoleh dengan memberikan 20 pertanyaan tertutup untuk mencari tahu bagaimana gaya belajar memengaruhi proses pembelajaran di kelas Bahasa Inggris (28 guru). Penelitian ini menemukan bahwa guru memahami keragaman gaya belajar siswa, sehingga mereka mengadopsi gaya belajar siswa dalam pengajaran mereka. Guru juga sepakat menggunakan kelompok diskusi ketimbang perkuliahan tradisional dengan mengintegrasikan Teknologi Informasi dan Komunikasi (TIK). Dapat disimpulkan bahwa persepsi guru terhadap gaya belajar siswa meningkatkan kepedulian mereka dalam mengembangkan metode mengajar yang beragam sesuai keragaman belajar siswa. Keywords: Students? learning style, teaching style